2019
DOI: 10.1111/resp.13538
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification for short‐term mortality at hospital admission for acute exacerbations of COPD

Abstract: Background and objective: Exacerbations of chronic obstructive pulmonary disease (ECOPD) are associated with increased in-hospital and short-term mortality. Developing an easy-to-use model to predict adverse outcomes will be useful in daily clinical practice and will facilitate management decisions. We aimed to assess mortality rates and potential predictors for short-term mortality after severe ECOPD. Classification and Regression Tree (CART) model was used to identify predictors of adverse outcome. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…For instance, Sprooten et al, in a contemporary cohort of patients hospitalized with COPD, showed that despite the progress in the management of COPD exacerbations over the past 30 years, severe COPD exacerbations remain highly lethal with 1 in 10 patients dying in hospital from complications related to their exacerbation (and 16% dying within 90 days of hospitalization) and 1 in 3 patients requiring mechanical ventilation for hypercapnic respiratory failure. 3 Importantly, the investigators found that these adverse events could be accurately predicted by measuring the patient's arterial carbon dioxide tension (PaCO 2 ) at the time of hospital admission. Mortality (from ventilatory failure) could be avoided (with modern treatment) when patients' PaCO 2 was less than 60 mm Hg, whereas mortality was extremely high when patients' PaCO 2 was 70 mm Hg or greater.…”
Section: Acute Exacerbations Of Copdmentioning
confidence: 99%
“…For instance, Sprooten et al, in a contemporary cohort of patients hospitalized with COPD, showed that despite the progress in the management of COPD exacerbations over the past 30 years, severe COPD exacerbations remain highly lethal with 1 in 10 patients dying in hospital from complications related to their exacerbation (and 16% dying within 90 days of hospitalization) and 1 in 3 patients requiring mechanical ventilation for hypercapnic respiratory failure. 3 Importantly, the investigators found that these adverse events could be accurately predicted by measuring the patient's arterial carbon dioxide tension (PaCO 2 ) at the time of hospital admission. Mortality (from ventilatory failure) could be avoided (with modern treatment) when patients' PaCO 2 was less than 60 mm Hg, whereas mortality was extremely high when patients' PaCO 2 was 70 mm Hg or greater.…”
Section: Acute Exacerbations Of Copdmentioning
confidence: 99%
“…The severity of COPD exacerbations is largely determined by dyspnoea, and the most effective (life‐preserving) therapies are aimed at reducing the work of breathing and enhancing ventilation . Thus, Sprooten et al ’s finding that significant hypercapnia (at a threshold of 9.1 kPa or 69 mm Hg) was the leading predictor of mortality and that almost all survivors had PaCO 2 levels below 8.2 kPa (61 mm Hg) aligns with clinical experience . This is a relatively simple message but one that has important implications.…”
mentioning
confidence: 94%
“…In a recent publication in Respirology , Sprooten et al address these concerns of existing decision rules by applying a method called Classification And Regression Tree (CART) to predict the risk of in‐hospital, as well as 90‐day, mortality in patients who were hospitalized for AECOPD . As noted previously, the current off‐the‐shelf decision rules are largely based on well‐established statistical principles such as multivariate regression analysis.…”
mentioning
confidence: 99%
See 2 more Smart Citations